Strategies For Developing Human Resources At Bumdes Bersama Jaya To Optimize The Economic Potential Of Village - Elsa Fitri; Agusdin; Mukmin Suryatni (LP2M IAIN Palopo, 2026)
This study aims to analyze human resource development strategies at BUMDes Bersama Jaya in order to optimize the economic potential of the village. The research approach used is qualitative with data collection techniques through in-depth interviews, observation, focus group discussions (FGD), and documentation studies. There were nine informants in this study, consisting of government officials, BUMDes managers, and community members involved, namely village and regional government officials, BUMDes administrators, and BUMDes partner communities. Data analysis was performed using Force Field Analysis (FFA) to identify and map the driving and restaining factors of BUMDes HR development. The results of the study show that the main driving factors for BUMDes human resource development come from external and social factors. Meanwhile, the dominant inhibiting factors include dysfunctional organizational structures, limited technical capacity of administrators, lack of ongoing training, non-standardized financial administration and reporting systems, and weak supervision and evaluation. Based on the FFA results, the human resource development strategy for BUMDes Bersama Jaya is directed at two main focuses, namely maintaining driving factors and weakening inhibiting factors through role classification strategies, financial and administrative capability strategies, institutional strategies, continuous learning strategies, and human resource strategies oriented towards governance. These strategies are expected to create a balance of forces for change so that BUMDes human resource development can proceed more effectively and sustainably.